Non-Instantaneous Impulsive Fractional Neutral Functional Stochastic Integro- Differential System with Measure of Non-Compactness - Malar, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This work focuses on existence results of fractional order stochastic non-instantaneous impulsive neutral functional integro-differential equation with infinite delay. The results are obtained by using the Hausdorff measure of non-compactness, fractional calculus, stochastic analysis techniques and fixed point theorems. Finally, examples are given to illustrate the obtained theory.